Personal and contextual components of resilience mediate risky family environment's effect on psychotic‐like experiences. Issue 6 (23rd December 2020) - Rossi, Rodolfo; Collazzoni, Alberto; Talevi, Dalila; Gibertoni, Dino; Quarta, Eleonora; Rossi, Alessandro; Stratta, Paolo; Di Lorenzo, Giorgio; Pacitti, Francesca
Abstract: Background: Psychotic‐like experiences (PLEs) index an increased risk for subsequent psychotic disorders. A risky family environment is a well‐established risk factor for PLEs; however, different contextual and personal resiliency factors may differentially mediate its effect on PLEs. Objective: In this study, we propose a two‐dimensional model of resilience. Our aim is to address separately the mediational role of personal and contextual resiliency factors between a risky family environment and PLEs in a community sample. Methods and materials: Five‐hundred University students completed an on‐line questionnaire, including the Resilience Scale for Adults (RSA), the 16‐item version of the Prodromal Questionnaire (iPQ‐16) and the Risky Family Questionnaire (RFQ). Mediation was assessed using Structural Equation Modelling with bootstrapping estimation of indirect effect. Results: The direct effects of personal and contextual resilience on PLEs were respectively −0.69 [−0.97, −0.41] ( P < .001) and − 0.19 [−0.58, 0.20] (ns); the indirect effect through personal resilience was 0.03[0.01, 0.04] ( P < .001). Personal resilience mediated 27.4% of the total effect of risky family environment on PLEs. Discussion: Personal resilience, as opposite to contextual resilience, mediates the effect of a risky family environment on PLEs. Low personal resilience may represent an individual risk factor that transmits the effect of risky family environment on PLEs and could represent a central aspect of individualized prevention and treatment strategies.